2022
DOI: 10.3389/fonc.2022.974257
|View full text |Cite|
|
Sign up to set email alerts
|

MRI radiomics predicts progression-free survival in prostate cancer

Abstract: ObjectiveTo assess the predictive value of magnetic resonance imaging (MRI) radiomics for progression-free survival (PFS) in patients with prostate cancer (PCa).Methods191 patients with prostate cancer confirmed by puncture biopsy or surgical pathology were included in this retrospective study, including 133 in the training group and 58 in the validation group. All patients underwent T2WI and DWI serial scans. Three radiomics models were constructed using univariate logistic regression and Gradient Boosting De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…More importantly, the APT value combined with the ADC value significantly improved the performance of fMRI in diagnosing RF, with an AUC of 0.93. This finding suggests that the combination of multiple fMRI sequence will further improve the diagnostic sensitivity of moderate-to-severe fibrosis [40‒42], with different MRI sequences perhaps reflecting different microscopic pathological changes. The combination of multiple MR parameters provides more comprehensive information on renal morphology, function, and tissue microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the APT value combined with the ADC value significantly improved the performance of fMRI in diagnosing RF, with an AUC of 0.93. This finding suggests that the combination of multiple fMRI sequence will further improve the diagnostic sensitivity of moderate-to-severe fibrosis [40‒42], with different MRI sequences perhaps reflecting different microscopic pathological changes. The combination of multiple MR parameters provides more comprehensive information on renal morphology, function, and tissue microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the study of Yan et al a DL-based radiomics signature was developed and externally validated, displaying C-index of 0.802 in both primary and validating cohorts and outperformed psCAPRA score (0.677) [37]. Interestingly, Jia et al reported that their hybrid model (radiomics features /clinical data) performed the best in predicting PFS (AUCs: 0.926 and 0.917 for training and validation groups) [38]. More recently, An et al built a combined model (clinical data, contrast-enhanced ultrasound-CEUS-, MRI radiomics) showing the highest predictive value (AUC: 0.91 and 0.93 in external validation) compared to clinical or CEUS and MRI radiomics and a nomogram was constructed [39 ▪▪ ].…”
Section: Radiomics and Prostate Cancermentioning
confidence: 99%
“…In addition, in the study of Yan et al a DL-based radiomics signature was developed and externally validated, displaying C-index of 0.802 in both primary and validating cohorts and outperformed psCAPRA score (0.677) [37]. Interestingly, Jia et al reported that their hybrid model (radiomics features /clinical data) performed the best in predicting PFS (AUCs: 0.926 and 0.917 for training and validation groups) [38]. More recently, An et al & ]) published between 2017 and 2020.…”
Section: Postsurgical and Post-radiation Biochemical Recurrencementioning
confidence: 99%
“…Radiomics and artificial intelligence (AI) are emerging tools for implementing precision medicine in prostate cancer [1] , [2] , [3] . Previous studies have demonstrated the potential of pre-treatment MRI or PET-based radiomic features to predict biochemical recurrence (BCR) [4] , [5] , [6] , [7] , [8] , which can affect up to 50 % of patients within ten years of radiation therapy (RT) [3] . Radiomic features also hold promise to assess early post-RT treatment response accurately, complementing the standard blood-based prostate-specific-antigen (PSA) test [1] , [3] .…”
Section: Introductionmentioning
confidence: 99%